Social Safety Nets in World Bank Lending and Analytical Work : FY2002–2007 - Andrews, Colin (World Bank, Washington, DC, 2012)
During FY 2002-2007 the World Bank engaged with 118 countries on social safety net (SSN) issues, providing lending in 68, analytic products in 86, training in 87, and a combined package of all three services in 42. A review of these safety net activities shows a strong diversity with respect to the regions, types of intervention, sectors and financing instruments. This reflects evolving thought within the Bank with respect to the role of safety nets in broad development strategies, not just immediate or temporary programs. The findings of the portfolio review take into account all project and analytic documents where a thematic code of 'social safety nets' was assigned. The analysis shows a noticeable variability over time, particularly as the portfolio expanded when large or multiple countries faced economic crises. The regional distribution of safety net activities reflects the dominance of Latin America, with emerging activities in the African and South Asian context.